Intergenerational effects of trade liberalization - Erhan Artuç (TÜSİAD-Koç University Economic Research Forum, 2009)
2002 Pew Global Attitudes survey shows that workers' support for free trade decreases with age. The relation between age and supporting free trade is a phenomenon previously unexplored by economists. We study distributional effects of trade liberalization, in particular age and gains from free trade, using a dynamic structural general equilibrium model. The method we use here is complimentary to Artuc, Chaudhuri and McLaren (forthcoming), and can handle a much richer treatment of ex-ante, endogenous and unobserved worker heterogeneity. This more efficient method allows us to calculate distributional effects of trade liberalization in detail but it requires a completely different estimation strategy, which comes at a cost of more computation time and stronger assumptions on workers' expectations. After estimating the structural model with U.S. data sets NLSY and CPS, we simulate a hypothetical trade liberalization in metal manufacturing sector (which has been especially vulnerable to trade shocks in the past, the steel industry in particular). We show gradual adjustment of labor allocation, wages and prices in response to this trade shock. We find a mirror effect where very young workers in the metal sector are moderately worse off and older workers are extremely worse off, while young workers in manufacturing sector are moderately better off and older workers are extremely better off.
Keywords: F1; D58; J2; J6; 330; Trade Liberalization; Sectoral Mobility; Labor Market Equilibrium; Außenhandelsliberalisierung; Verteilungswirkung; Generationenbeziehungen; Allgemeines Gleichgewicht; Schätzung; USA